DESAIN ANTENA MIKROSTRIP BINTANG 30 UNTUK ACCESS POINT PERANGKAT IOT DI ATP MALANG - Ajeng Kusuma Dewi; Muhammad Fauzan Edy Purnomo; Endah Budi Purnomowati (Jurnal Mahasiswa TEUB, 2023)
The development of the internet is very fast with communicating freely. One of the technologies that take advantage of the internet is the Internet of Things which is the development of network communications from connected objects using the internet to exchange data into information. IoT requires wireless communication. The access point is part of wireless communication Devices that can be used as support for access points are antennas. One type of antenna is the microstrip antenna which is an antenna that has small dimensions and is flexible. Agro Techno Park (ATP) is the development of agricultural technology. Jatikerto Malang garden ATP has utilized IoT technology to help cultivate premium melon commodities, but the network infrastructure still needs to be improved. The 30-star microstrip antenna was simulated using CST Studio Suite 2019, considering several VSWR parameters spanning < 2, Gain > 3, Return Loss < -10, Efficiency > 80, and having linear polarization. Antenna implementation testing is carried out by considering the speed, range, and transmission power parameters of the antenna that has been fabricated. The test results show that the 30-star microstrip antenna has a VSWR value of 1.65, Return Loss -12 dB, Gain 4, Group Delay -2.5, Axial Ratio 40, Directivity 4, 90% efficiency, and linear polarization. The result of implementing the antenna on the transmission speed increased by 24.14% and has a range reaching a maximum distance of 72.41 meters exceeding the area of the ATP Jatikerto Malang melon garden with low power.Kata Kunci— Access Point, Antena Mikrostrip, dan Internet of Things